The Ethics of Armed Conflict - A Cosmopolitan Just War Theory - W. Lango, John (Edinburgh University Press, 2014)
Develops generalised just war principles that can be applied to all forms of armed conflict. This title was made Open Access by libraries from around the world through Knowledge Unlatched.